Proceedings of the 36th Annual ACM SIGPLAN-SIGACT Symposium on Principles of Programming Languages 2009
DOI: 10.1145/1480881.1480911
|View full text |Cite
|
Sign up to set email alerts
|

Semi-sparse flow-sensitive pointer analysis

Abstract: Pointer analysis is a prerequisite for many program analyses, and the effectiveness of these analyses depends on the precision of the pointer information they receive. Two major axes of pointer analysis precision are flow-sensitivity and context-sensitivity, and while there has been significant recent progress regarding scalable context-sensitive pointer analysis, relatively little progress has been made in improving the scalability of flow-sensitive pointer analysis.This paper presents a new interprocedural, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(47 citation statements)
references
References 55 publications
0
47
0
Order By: Relevance
“…On the contrary, empirical studies have validated that flow-sensitivity in program analysis strongly improves precision (see, e.g. [24]). …”
Section: Security Type Systemsmentioning
confidence: 99%
“…On the contrary, empirical studies have validated that flow-sensitivity in program analysis strongly improves precision (see, e.g. [24]). …”
Section: Security Type Systemsmentioning
confidence: 99%
“…(It does not, however, model languages such as C or C++ that can create pointers through an address-of operator. The techniques used in that space are fairly different-e.g., [8,9]although our main hybrid approach is likely to be applicable. Also, even though we model regular object fields and static methods, we omit static fields.…”
Section: Background: Parameterizable Modelmentioning
confidence: 99%
“…Despite the pessimism, it is shown that a precise pointer analysis helps several clients, such as typestate verification [Fink et al 2008], security analysis [Chang et al 2008], bug detection [Guyer and Lin 2005], and the analysis of multithreaded programs [Salcianu and Rinard 2001]. As a result, there has been renewed interest in the area of flow-sensitive pointer analysis, and the scalability of such analyses, particularly for C programs, has been greatly improved [Hardekopf and Lin 2011;Li et al 2011;Lhoták and Chung 2011;Hardekopf and Lin 2009;Kahlon 2008]. Our bit of contribution here is to improve it further with parallelization and controlled approximation.…”
Section: Related Workmentioning
confidence: 99%